A Review of Antithrombotic Therapy and the Rationale and Design of the Randomized Edoxaban in Patients With Peripheral Artery Disease (ePAD) Trial Adding Edoxaban or Clopidogrel to Aspirin After Femoropopliteal Endovascular Intervention. (April 2015) - Tangelder, Marco J. D.; Nwachuku, Chuke E.; Jaff, Michael; Baumgartner, Iris; Duggal, Anil; Adams, George; Ansel, Gary; Grosso, Michael; Mercuri, Michele; Shi, Minggao; Minar, Erich; Moll, Frans L.
Compared with the coronary setting, knowledge about antithrombotic therapies after endovascular treatment (EVT) is inadequate in patients with peripheral artery disease (PAD). Based on a review of trials and guidelines, which is summarized in this article, there is scant evidence that antithrombotic drugs improve outcome after peripheral EVT. To address this knowledge gap, the randomized, open-label, multinational e doxaban in patients with P eripheral A rtery D isease (ePAD) study ( ClinicalTrials.gov identifier NCT01802775) was designed to explore the safety and efficacy of a combined regimen of antiplatelet therapy with clopidogrel and anticoagulation with edoxaban, a selective and direct factor Xa inhibitor, both combined with aspirin. As of July 2014, 203 patients (144 men; mean age 67 years) from 7 countries have been enrolled. These patients have been allocated to once-daily edoxaban [60 mg for 3 months (or 30 mg in the presence of factors associated with increased exposure)] or clopidogrel (75 mg/d for 3 months). All patients received aspirin (100 mg/d) for the 6-month duration of the study. The primary safety endpoint is major or clinically relevant nonmajor bleeding; the primary efficacy endpoint is restenosis or reocclusion at the treated segment(s) measured at 1, 3, and 6 months using duplex ultrasound scanning. All outcomes will be assessed and adjudicated centrally in a masked fashion. The ePAD study is the first of its kind to investigate a combined regimen of antiplatelet therapy and anticoagulation through factor Xa inhibition with edoxaban.